Morphological and chemical characterization of mineral concretions in the freshwater bivalve Anodonta cygnea (Unionidae) - Hinzmann, Mariana F. (2015)
The freshwater mussel Anodonta cygnea is commonly used as a model organism for biomineralization studies, its peculiar morphofunctional properties also make it an excellent environmental biomonitor. The first detailed on the calcareous concretions from gill and mantle tissue, as well as fluids of the freshwater bivalve A. cygnea, supported by histological, scanning, spectrometry, and spectroscopy analyses. Through these analyses, the morphology, structure, and chemical characterization of these biomineral concretions were accomplished. The concretions represent a high percentage of the dry weight of these organisms. In gill tissue, it can reach up to 50% of dry weight prior to reproductive maturity. Analysis of elemental composition of the tissue concretions showed the presence of calcium and phosphate, as main components, associated with other residual elements like iron, manganese, magnesium, and zinc. Concretions are arranged in concentric alternated layers of organic and inorganic matrix. The shape and size of the concretions vary substantially, from very small, less than 1 µm diameter with very regular round structure, found mainly in the mantle tissue, to more than 50 µm length with irregular globular clusters, found predominantly in the gills. The microstructural organization is of a hydroxyapatite polymorphism in the mantle, in contrast to the gills, which exhibit irregular structure and carbonated hydroxyapatite polymorphism. These differences are supported by higher contents of dinitrogen pentoxide, magnesium, and iron in the mantle concretions, but higher contents of manganese and zinc in the gills. Furthermore, the results indicate that the mineral concretion formation in A. cygnea is a hemocytes reaction to particle or toxic invasions. A second relevant role, concerns the close involvement of these microspherules on the adult and larval shell calcification.